Prediction of the coexistence of rail head check initiation and wear growth. (July 2018) - Zhou, Yu; Han, Yanbin; Mu, Dongsheng; Zhang, Congcong; Huang, Xuwei
Highlights: A method is presented for predicting the coexistence of rail head check (HC) initiation and wear. The HC initiation was discretized into the fatigue accumulation under variable amplitude load by wear. Wear changed the HC initiation position to rail center and surface and reduced its initiation life for heat-treated rail. The development of the fatigue damage was nonlinear from slow to fast because of wear. Abstract: A method for predicting the coexistence of the rail head check (HC) initiation and wear growth was presented to divide the continuous process of HC initiation and wear growth into many of the same discrete processes, each of which included wear and fatigue damage by wheel/rail stick–slip contact, wear-induced rail profile evolution, cumulative fatigue damage until a random material point in the rail reached the fatigue failure criterion. The method was applied to predict HC initiation for a U75V heat-treated rail, this being the sharp curve high rail used in China's heavy-haul railway, and was compared with the method considering no wear and validated by field tests. The result shows that the HC initiation life was about 2.17 × 10 5 wheel cycles and the average vertical wear growth rate was about 4.2651 μm/10 4 wheel cycles, values which were close to the field observation. Because the wear growth and profile evolution, the HC initiation position was closer to the rail center than when using the method considering no wear and the development of the fatigue damage was nonlinear from slow to fast .